Ii International Seven Multidisciplinary Congress 2023
DOI: 10.56238/homeinternationalanais-040
|View full text |Cite
|
Sign up to set email alerts
|

Profile of morbimortality by stroke in Brazil between 2015 and 2020

Abstract: Stroke is the second leading cause of death worldwide, including Brazil¹,2. It is a more common condition in the elderly, but it has an increasing prevalence in young adults due to the development of risk factors that were typically attributed to older ages3. Risk factors can be categorized into non-modifiable (race, ethnicity, gender and age) and modifiable (arterial hypertension, obesity, diabetes mellitus, smoking and alcoholism), both contributing to distinct trends in incidence and mortality from stroke4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We found that in Brazil the number of overweight patients with their fi rst stroke was greater than the number with normal BMI and stroke. Most of the former had less than eight years of schooling, belonged to social class C and were signifi cantly more physically inactive, often associated with obesity, which aff ects about 41 million people (25.9%) [48,49].…”
Section: Algeria Egypt Revisionmentioning
confidence: 99%
“…We found that in Brazil the number of overweight patients with their fi rst stroke was greater than the number with normal BMI and stroke. Most of the former had less than eight years of schooling, belonged to social class C and were signifi cantly more physically inactive, often associated with obesity, which aff ects about 41 million people (25.9%) [48,49].…”
Section: Algeria Egypt Revisionmentioning
confidence: 99%